Risk of treatment-related deaths with vascular endothelial growth factor receptor tyrosine kinase inhibitors: a meta-analysis of 41 randomized controlled trials - Hong, Shaodong (Dove Medical Press, 2014)
BACKGROUND: Vascular endothelial growth factor receptor (VEGFR) tyrosine kinase inhibitors (TKIs) have widely been used in advanced cancer. However, these drugs may also lead to serious adverse events. The present meta-analysis aimed to determine the overall incidence and risk of deaths due to VEGFR-TKIs with more detailed subgroup analysis. MATERIALS AND METHODS: PubMed, Web of Science, and Cochrane databases were searched for randomized controlled trials (RCTs) that compared VEGFR-TKIs with non-VEGFR-TKIs in the treatment of solid cancer. Pooled incidence, odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using random-effects or fixed-effects models based on the heterogeneity of included trials. RESULTS: A total of 14,139 participants from 41 RCTs were enrolled. The pooled incidence of death due to VEGFR-TKIs was 1.9% (95% CI: 1.6%–2.3%) with an OR of 1.85 (95% CI: 1.33–2.58; P<0.01) when compared with control groups. On subgroup analysis, significantly increased risk of death was found in patients with nonsmall-cell lung cancer (OR: 2.37; 95% CI: 1.19–4.73; P=0.01) and colorectal cancer (OR: 2.84; 95% CI: 1.02–7.96; P=0.05). Among different VEGFR-TKIs, sorafenib and sunitinib had significant risk of death when compared with control arms, respectively. VEGFR-TKIs in combination with other antineoplastic agents, but not VEGFR-TKI monotherapy, significantly increased the risk of treatment-related deaths. No heterogeneity was noted across all the prespecified subgroups regarding ORs. CONCLUSION: The present work pointed out a significantly increased risk of death due to VEGFR-TKIs. Close monitoring should be emphasized in patients receiving these drugs.